"An epoch-making and blessed moment in the history of medicine" -thoughts on international health equity and the Nobel prize in medicine - Zachary M. Linneman; David J. Satin (BMC, 2021)
Abstract The Nobel Prize in Physiology or Medicine is a prestigious award given every year for ostensibly the most important discovery in the field. Prizes in Medicine have typically gone to honor foundational knowledge rather than measurable impact. Two recent examples from global health (a rotavirus vaccine, child growth standards) offer alternatives for what might be lauded in medicine. These two examples and historical achievements regarding cholera and smallpox are worthy but do not fall within the scope of Nobel awards for Peace or Economics. The COVID-19 pandemic gives a new context for the idea that discovery and implementation are both keys to medicine. New patterns that redefine achievement in medicine could emerge by Nobel Prize precedent to promote greater health equity and international collaboration.